PENINGKATAN KEMAMPUAN BERPIDATO SISWA KELAS VI SD DENGAN MODEL PJBL (PROJECT BASED LEARNING) BERBANTUAN MEDIA AUDIO VISUAL - Rosyada, Dina (Universitas Muria Kudus, 2023)
One of the problems in learning Indonesian is the low competence in giving speeches. To overcome this, the right learning model is one of them with the Project Based Learning (PjBL) model assisted by audio-visual media. The purpose of this study was to improve the learning outcomes of speech skills by applying the PjBL learning model assisted by audio-visual media in class VI B SD Negeri 1 Sengonbugel.The approach in this study uses the classroom action research method. The research data was taken from the students' speech activities. Data collection techniques in this study were observation, interviews, and documentation. Data analysis was carried out by observing student activities in implementing the speech learning process using the PjBL model assisted by audio-visual media. The result data was transcribed in tabular form. This research was carried out in two cycles, namely cycle I and cycle II. Each cycle consists of four stages, namely planning, observation, action, and reflection.The results showed that the results of students' speaking abilities included linguistic and non-linguistic abilities. Overall, students' speaking ability through PjBL learning model assisted by audio-visual media has increased by 46% from 38% in the first cycle to 84% in the second cycle. From the results of this classroom action research, it can be said that the application of the PjBL learning model assisted by audio-visual media can improve the speaking ability of sixth grade students of SD Negeri 1 Sengonbugel.